Potential Screening of Spray Dried Solid Dispersion of Orlistat using Three Dimensional Solubility Parameter - Payghan, Dr. Santosh Ambadas (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Hansen solubility parameters (HSPs) have been used to predict the miscibility of a drug with excipients/carriers in solid dispersions. This study investigated whether the miscibility of a drug and its coformer components, as predicted by theoretical miscibility tools, this eventually led to the concept of a three dimensional solubility parameter (E). This is to determine whether the process parameters of the laboratory-scale spray dryer affects the solubility behavior and physical stability of the solid dispersion. Group-contribution method for the estimation of HSPs of pure organic compounds is presented by characteristic groups ensures the prediction of HSP for a broad series of organic compounds including those having complex multi-ring, heterocyclic, and aromatic structures. The predictions are exclusively based on the molecular structure of compounds, and no experimental data are needed. Materials and Methods: Theoretical prediction of solubility Fedor’s Method/Fedor’s Substituent Constants, Hoy’s method/Hoy’s Molar Attractions, Van Krevelen’s solubility parameters the calculation of solubility parameter, and molar volume Van Krevelen’s method, which is based on experimental molar volume measured cm3Mol-1, theoretical screening and comparison of orlistat by 3D parameter, formulation of spray dried cocrystals, optimization of spray drying process parameters. Result and Discussion: The selected coformer was based on HSP by which three methods are used such as Fedor’s methods, van Krevelen’s methods, and hoys methods. Based on their given value the selection of coformer was done by Krevelen’s Δδ≤5MP and Greenhalgh Δδ≤7MP. Proposed structure of orlistat was developed using ChemSketch software. The thorough understanding of the structure of API and coformer is required to locate correctly the hydrogen bonding. Coformer selection was done based on hydrogen bonding in structure. The surface morphology studies revealed that the solid dispersion was closely compacted into small spherical form. Conclusion: Considerable improvement in the dissolution rate of orlistat from optimized formulation was due to an increased solubility that is attributed to the supersaturation from the fine cocrystals is faster due to the large specific surface area of small particles and prevention of phase transformation to pure orlistat.